Poverty and Terrorism in Northern Nigeria: Reflections and Notes on the Manipulation of the Almajirai System and its Implication for National Development - Emmanuel Osewe Akubor (Modern Africa, 2016)
Scholars have posed a relation between Poverty, Ignorance and Terrorism. This is based on the increasing and heightening level of terrorist activities in most parts of the world, which has been linked to the ability of some powerful forces and actors manipulating the minds and hands of those affected by poverty (both material and intellectual) in society to engage in terrorist acts. Data obtained from primary and secondary sources were deployed to carry out a study with an analytical and narrative historical method. Findings indicate that in the case of Nigeria, with specific reference to the northern part of Nigeria, these actors (often wealthy, influential and disgruntled political and religious persons) deliberately manipulated the almajirai system to perpetuate terrorism. It also discovers that this act has in one way or another hampered the socio-economic development of the area in particular and the nation at large. The main reason is that human and intellectual resources, which would have been channelled towards building the nation, have been diverted to destructive tendencies without those involved knowing this under the guise of either liberation movement or fighting for freedom. It can therefore be concluded that unless more drastic measures are taken, the country may face even more severe dangers.